A comparison of African American and Caucasian stimulant users in 12-step facilitation treatment. Issue 3 (3rd July 2017) - Peavy, K. Michelle; Garrett, Sharon; Doyle, Suzanne; Donovan, Dennis
ABSTRACT: Engagement in 12-step meetings and activities has been shown to be a powerful aid to recovery from substance use disorders. However, only limited attention has been given to ethnic and racial differences in attitudes toward 12-step and involvement. This study utilized data from a large multisite trial testing the effectiveness of a 12-step facilitation therapy with stimulant-dependent treatment seekers. We compared baseline differences and treatment outcomes between African American and Caucasian participants. A select few baseline differences were found (i.e., African Americans reported higher levels of spirituality than Caucasians; African American participants indicated more perceived benefits of 12-step involvement; Caucasians were more likely to endorse future involvement in 12-step). There were no outcome differences (e.g., substance use outcomes, 12-step meeting attendance). The tested intervention produced similar outcomes for both groups, indicating that it may be useful across racial categories.